Aesthetics of Comfort: A Third Moment in Costa Rican Histories of Tropical Architecture - Solano Meza, Natalia (2020)
Histories of tropical architecture in Costa Rica could be constructed around three moments: the settlement of the United Fruit Company (UFCO) in 1889, the visit of Otto H. Koenigsberger, director of the Department of Development and Tropical Studies during the opening of the School of Architecture of the University of Costa Rica in 1970, and finally, the constitution of a set of formal principles and images guiding the work of many architects in Costa Rica and justified by the need to provide comfort—or sensory contentment—in the tropical climate: an aesthetics of comfort. Although it is often considered a technical term, in our work, comfort operates also as a historical and aesthetic concept. Our research suggests that the aesthetics of comfort has been disseminated through journals and exhibitions since the 1990s, while also absorbing experiences from the two previous moments. Consequently, it cannot be separated from histories of colonialism, extractivism, hygiene, and interventionism. It is present, although in different forms and with different purposes, in the work of architects such as Édgar Brenes, Víctor Cañas and Bruno Stagno. In the media, their prominent achievements are presented as the result of responsiveness to nature, building technology, site adaptation and the ability to offer contentment. From our analysis, we claim that the aesthetics of comfort functions as a validation mechanism, one that praises technical knowledge and formal adaptation but tends to ignore histories of colonialism and knowledge production.